Pola Gerak Tari Katipak Pada Ritual Babukokng Suku Dayak Ma'amp Di Desa Sebabas Kecamatan Nanga Mahap Kabupaten Sekadau - Victoria Ria Nopiantika; Oktaviari Satrianingsih, Aline Rizky; Oktariani, Dwi (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
The Babukokng ritual is a death ritual of the Dayak Ma'amp Tribe in Sebabas Village, Nanga Mahap District, Sekadau Regency. This ritual is carried out for people who have faith in the Almighty, and people who are considered to have had rank or merit to the village, carried out for 2 days, starting from the perabus location accompanied by barantu batunu, followed by bukokng ansau, bukokng batamak, bukokng alu, bukokng nyamut buah mansak, and pemasar. Katipak dance has 3 movement patterns called ngemak movements, accompanied by katipak music. Katipak dance is danced by adult male dancers with the number of 3, 5, or 7 people based on laboh bukokng, and has 1 sacred floor pattern with a circle shape that is believed to be a whirlpool to prevent evil spirits. This research uses a qualitative form with descriptive research methods and an ethnocoreological approach. Data collection was done by observation, interview, and documentation. The technique of testing the validity of data with extended observation and source triangulation.